103k views
4 votes
Which of the following is the solution set of the given equation?

(x - 3) - 2(x + 6) = -5
A) {-10}
B) {-4}
C) {8}

1 Answer

1 vote
x= -10

first you distribute the -2 throughout (x+6) which then becomes, -2x -12
After you’ve done that plug it in the equation, the equation should be, x-3-2x-12=-5
Now combine like terms. After it should look like, -x - 15 = -5, Add 15 to both side. It should be, -x = 10
Finally divide by -1 on both sides and that should give you x= -10



sorry that was a long explanation
User Bert Te Velde
by
6.1k points